Analisis Kemampuan Generalisasi Matematis Siswa SMP Kota Cilegon - Muslimah, Amelia; Pujiastuti, Heni; Mustafa, Ade Nandang; Novaliyosi, (Media Pendidikan Matematika, 2025)
This study aims to analyze the mathematical generalization ability of junior high school students in Cilegon City on the topic of relations and functions. Mathematical generalization ability is an important component of higher-order thinking that includes the ability to recognize patterns, express regularities, and represent mathematical relationships in symbolic form. The method used was descriptive quantitative, involving 368 students from 50 schools that are members of the Mathematics Subject Teachers Association (MGMP) of Cilegon City. The research instrument consisted of six open-ended questions developed based on three indicators of generalization ability proposed by Mason, Sitorus, and Sutirna (2023): perception of generality, expression of generality, and symbolic and manipulation of generality. Data were analyzed descriptively through the calculation of mean scores and ability category classification. The results of the study show that students’ mathematical generalization ability is in the moderate category with an average score of 2.08. The indicators of perception of generality and expression of generality are also in the moderate category, while symbolic and manipulation of generality falls into the low category. These findings indicate that students are able to recognize patterns and express simple relationships, but still experience difficulties in constructing formal symbolic representations. Based on these results, mathematics learning needs to be more oriented toward exploration, conceptual reasoning, and the use of interactive visual media to improve students’ symbolic representation skills and functional understanding.